F Formulasi Dan Evaluasi Fisik Sediaan Deodoran Gel Kombinasi Ekstrak Kulit Jeruk, Teh Hijau Dan Buah Pepaya - Nugraha, Zen Achmad Redho; Budi, Setia; Yusri, Yusri (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Orange peel extract has antibacterial activity, green tea extract has antiperspirant activity and papaya extract has skin lightening activity so that the three extracts are combined and a deodorant gel preparation is made. The deodorant gel is expected to give a cool feeling and be fast in application. The basic carbomer concentration used in this study is 0.5% -2%. The purpose of this study was to obtain deodorant formulations with active plant substances and to obtain optimization of formulations and to see physical evaluations of deodorant gel preparations combined with extracts of orange peel, green tea and papaya fruit. The method used is a pre-experimental one case shot study. Deodorant gel combination of extracts of orange peel, green tea and papaya fruit was made into three formulations with different gelling agent variations, in formulation I used carbomer (0.5%), formulation II used carbomer (1.5%) and formulation III used carbomer (2%). Organoleptic test and homogeneity test have met the requirements. In the pH test, it was found that the three formulations were in accordance with the skin pH requirements. on the viscosity test, formulations II and III met the viscosity requirements. Spreadability test, formulation I was in accordance with the requirements of the gel. The adhesion test, the three formulations complied with the adhesive power requirements, the dry time test, the three formulations complied with the dry time test requirements. irritation test showed that the three formulations did not cause a reaction, which means that the three formulations were safe to use. The optimal formulation is formulation I as seen from the mean value of the evaluation test carried out.